MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN LEMBAR KERJA SISWA MELALUI WORKSHOP DI GUGUS SEKOLAH - Lilis Kustriani (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2019)
This research is a School Action Research (SAR) conducted at primary school (SD Negeri Kampung Sawah) in Bogor Utara District at Semester 2 of the 2017-2018 Academic Year. The research was conducted in two cycles, each cycle consisting of four stages, namely: planning, implementation, observation and reflection. The specified performance indicator is when a minimum score of 12 (quite active). In compiling the Student Worksheet it can be said to be successful. The aspects measured in the observation are the enthusiasm of the teacher, interaction with the teacher in the teacher's work group, group cooperation, activities in group discussion. The analysis found that there was an increase in teacher activity and competence in preparing the Student Worksheet from cycle I to cycle II. Achievement of performance indicators is in action II. Thus, it can be said that cluster activities can improve the competence of teachers in Kampung Sawah State Primary School, North Bogor District, Bogor City Semester 2 2017-2018 Academic Year. The teacher gave a positive response to the results of the workshop in the Cluster. The results showed that the preparation of Student Worksheets could improve the competence of teachers in Kampung Sawah Public Elementary Schools. Thus it can be suggested to supervisors, friends or other researchers to use cluster activities as a forum to improve teacher competencies that are carried out continuously. Cluster activities can increase the competence of public elementary school teachers in preparing student worksheets.